Edukasi Hama Dan Penyakit Serta Sosialisasi Pengenalan Cendawan Entomopatogen Beuveria Bassiana Sebagai Solusi Pengendalian Hama Pada Tanaman Pangan Di Desa Lamatti Riaja, Kecamatan Bulupoddo, Kabupaten Sinjai - Fauzan, Fauzan; Sulaeha, Sulaeha; Daud, itji Diana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity is entitled education on pests and diseases and socialization of the introduction of entomopathogenic fungi Beauveria bassiana as a solution for pest control in food crops. This community service aims to provide education about pests and diseases to the community, especially farmers. This community service activity was carried out in Lamatti Riaja Village, Bulupoddo District, Sinjai Regency. This activity is important to increase public insight into pests and diseases and solutions for controlling pests in food crops using Beauveria bassiana. The methods used are education and evaluation. The results of this community service can be seen that there has been an increase in public understanding regarding pests and diseases and how to control pests using Beauveria bassiana.